Pemberdayaan Masyarakat Pada Usaha Mikro Kecil Menengah Anugerah Foods Sentra Aneka Keripik di Desa Jungke Magetan - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi (Wisanggeni : Jurnal Pengabdian Masyarakat, 2021)
Community service programs are programs that aim to help the community without expecting anything in return. This service program seeks to help the Micro, Small, and Medium Enterprises (MSME) group "Anugerah Foods, Various Chips Center" located in Jungke Village, Karas District, Magetan Regency in dealing with various problems. Anugerah Foods is currently still constrained by a marketing strategy that still uses a personal selling strategy or is sold around Jungke Village. The main objective of this community service program is to provide innovation by introducing an online marketing system. The innovation introduced to Anugerah Foods is an online marketing strategy through a website, namely WordPress and social media in the form of Facebook and Instagram. By conducting visits and training on online strategy operations to Anugerah Foods members, it is our effort to convey innovation to be able to compete in the market and maintain good product quality. For students, this community service program is intended to fulfill entrepreneurial learning tasks and learn about entrepreneurship that they upload.